Unevenly mixed Romani languages. (October 2015) - Adamou, Evangelia; Granqvist, Kimmo
This study reports on language mixing in two Romani communities, with a century-long presence in Finland and in Greece respectively. A quantitative analysis of free-speech data shows that verbs from the contact languages, Finnish and Turkish, are systematically inserted into a dominant Romani speech with their respective Finnish and Turkish tense, mood, aspect, and person morphology. The insertion in language A of non-integrated single words from language B is atypical for classic code-switching and borrowing, but is a well-known mechanism in the creation of mixed languages. Unlike mixed languages, however, where no single dominant language can be identified, Romani is the main component in the corpora under study. We suggest that this type of Romani language mixing illustrates an early stage of mixed language formation that did not develop into an independent mixed language, owing to changes in the sociopolitical settings.